Evaluation Of Medicine Management at the UPTD Pharmacy Warehouse Manembo-Nembo Hospital Type C Bitung - Nelwan, Olga Enggelina; Bolang, Alexander Sam Leonard; Danes, Vennetia Ryckerens (International Publisher, 2023)
This study was conducted to determine how to evaluate drug management in the pharmaceutical warehouse of the UPTD Manembo-Nembo Hospital type C Bitung. This research uses qualitative research methods by conducting in-depth interviews, document review and observation. This research was conducted at the Pharmacy Warehouse of UPTD Manembo-nembo Hospital Type C Bitung which is located at Jalan SH Sarundajang, Manembo-nembo Tengah Village, Matuari District, Bitung City, North Sulawesi from April to June 2023. The informants of this research are those who have the authority to manage drugs in the Pharmacy Warehouse of the UPTD Manembo-nembo Hospital Type C Bitung. Such as the Head of the Pharmacy Installation, Head of the Hospital Pharmacy Warehouse, Hospital Director, Medical Support and Pharmaceutical Technical Personnel. The results of the study found that Drug Planning at the UPTD Manembo-nembo Hospital Type C Bitung has followed the Guidelines for Planning Drug Needs Regulation of the Minister of Health of the Republic of Indonesia Number 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals, Drug storage in the Pharmaceutical Warehouse UPTD Manembonembo Hospital Type C Bitung is in accordance with using 21 drug storage parameters used only 2 parameters that are not yet in accordance, namely that there are several boxes of drugs placed on the floor without using pallets on the floor and some drugs have not been placed on the shelves of the medicine cabinet, and Monitoring and evaluation is well underway.